2014
DOI: 10.1264/jsme2.me13113
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Anaerobic Bacteria to Chlorinated Solvents

Abstract: The aim of this research was to evaluate the effects of four chlorinated aliphatic hydrocarbons (CAHs), perchloroethene (PCE), carbon tetrachloride (CT), chloroform (CF) and 1,2-dichloroethane (1,2-DCA), on the growth of eight anaerobic bacteria: four fermentative species (Escherichia coli, Klebsiella sp., Clostridium sp. and Paenibacillus sp.) and four respiring species (Pseudomonas aeruginosa, Geobacter sulfurreducens, Shewanella oneidensis and Desulfovibrio vulgaris). Effective concentrations of solvents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Various approaches have been conducted to estimate the minimal maintenance energy in stable and nutrient-limited environments ( 9 ). Koenig et al indicated an energy requirement for response to stresses, because bacterial cells under lower energy-producing conditions were more sensitive to toxic solvents ( 18 ). In contrast, photosynthetic energy production in the light increased the viability of photosynthetic bacteria under nutrient-limited conditions ( 7 , 15 , 35 ).…”
Section: Non-dividing But Metabolically Active Statementioning
confidence: 99%
“…Various approaches have been conducted to estimate the minimal maintenance energy in stable and nutrient-limited environments ( 9 ). Koenig et al indicated an energy requirement for response to stresses, because bacterial cells under lower energy-producing conditions were more sensitive to toxic solvents ( 18 ). In contrast, photosynthetic energy production in the light increased the viability of photosynthetic bacteria under nutrient-limited conditions ( 7 , 15 , 35 ).…”
Section: Non-dividing But Metabolically Active Statementioning
confidence: 99%
“…Chlorinated organic solvents are known to inhibit bacterial growth rates, reduce membrane permeability, and damage nucleic acids . In studies using pure and mixed methanotrophic cultures, TCE exposure slowed both the metabolic and the cometabolic biotransformation rates of methane and dichloroethenes, respectively. , Chlorinated solvents have been reported to inactivate specific enzymes, such as cytochrome P450 related monoxygenases .…”
Section: Introductionmentioning
confidence: 99%
“…1 Organochlorine solvents are inhibitory to most anaerobic microbial processes with inhibitory potency increasing with decreasing water solubility. 2 Further, chlorinated methanes are inhibitory to microbial organohalide respiration of chlorinated ethanes and ethanes, 3,4 which can confound attempts to bioremediate sites polluted with solvent mixtures. In such a scenario, pretreatment to remove chlorinated methanes maybe necessary or an abiotic strategy maybe employed.…”
Section: ■ Introductionmentioning
confidence: 99%